Mixed-method assessment of caregiver feeding practices in early care and education centres during COVID-19 - Joanna Farrer Mackie; Heewon Gray; David Himmelgreen; Jennifer Marshall; Abbey Alkon; Russell Kirby (Cambridge University Press, 2023)
Abstract Objective: The COVID-19 pandemic changed early care and education (ECE) mealtimes. Feeding practices that support children's emerging autonomy may support children's healthy eating, but it is unknown whether and how COVID-19 changed feeding practices. This paper describes caregiver feeding practices in ECE centres in Florida during COVID-19. Design: A mixed-methods design was used to understand mealtime feeding practices. Survey and interview questions were developed based on the Trust Model. More than 7000 surveys were sent to ECE centres. Analysis included descriptive statistics for survey data and thematic analysis for interview data. Setting: This statewide study included teachers in all licensed and license-exempt ECE centres. Participants: Four hundred and thirty-one teachers completed a survey, and twenty-nine participated in follow-up interviews. Results: Surveys showed most teachers engaged in autonomy-supportive behaviours, such as letting children eat until they were finished (90 %). The most common controlling behaviour was praising children for cleaning their plates (70 %). The most common responses about changes to mealtimes were keeping physical distance and serving healthy food. Interview themes were Autonomy Support, Controlling Feeding Practices, Interactions are the Same, Interactions are Different, Physical Distancing and Healthy Eating. Conclusions: Mealtimes are a central part of the day for young children and teachers in ECE environments. COVID-19 continues to influence ECE routines as behaviour change remains the primary method of reducing the risk of COVID-19 in the absence of a vaccine for young children. Understanding teachers' practices and perspectives is important for reducing the risk of COVID-19 and supporting children's autonomy and healthy eating.